Sanksi Hukum Kepada Pemilik Kendaraan Yang Tidak Membayar Pajak Tahunan Kendaraan Bermotor - Rusdi Yunial; Noval Nanusa Gegoh Desky; Deni Febrian Akbari; Okna Periandi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
One of the most significant components of local taxes in increasing local revenue is the motor vehicle tax. The funds obtained from motor vehicle taxes are used to finance the development of each district or city. Thus, the collection of this tax revenue must be optimized as much as possible. This research is a normative and empirical legal study. There are several reasons why vehicle owners might not pay taxes: they are busy, they forget, their vehicle is still in the credit process, their vehicle is nearby, installments are more important, or their vehicle is old. Two types of administrative sanctions can be imposed on vehicle owners who do not pay the annual tax: increases and administrative sanction interest. To make it easier for taxpayers to pay their motor vehicle taxes, several new approaches need to be implemented. Efforts to improve the quality of human resources must be combined with increasing motor vehicle tax revenue.